Leadership Development in the Church: Inter-Disciplinary Methodology and Implications for Pastoral Formation - Kheng, Christina (Asian Horizons, 2024)
This article highlights issues that have arisen from leadership development in the Catholic Church particularly in terns of ambiguities and tensions in meaning and approaches. It discusses some problems associated with the ways in which secular and religious teachings on leadership have been appropriated and the underlying lack of attention to inter-disciplinary methodology. To address these problems, the article points out the importance of attending to philosophical foundations and outlines what a common foundation might be. The resulting orientations for leadership theory are then highlighted, along with suggestions on how secular and religious sources might be reformulated. Thereafter, the implications for leadership development are discussed.